Gain of Function of Ion Channel TRPV1 Exacerbates Experimental Colitis by Promoting Dendritic Cell Activation - Lina Duo; Ting Wu; Ziliang Ke; Linghan Hu; Chaohui Wang; Guigen Teng; Wei Zhang; Weihong Wang; Qing Ge; Yong Yang; Yun Dai (Elsevier, 2020)
Dysregulated mucosal immunity plays an essential role in the pathophysiology of inflammatory bowel disease (IBD). Transient receptor potential vanilloid 1 (TRPV1) is a Ca2+-permeable ion channel that is implicated in modulating immune responses. However, its role in the pathogenesis of intestinal inflammation remains elusive. Here, we found that TRPV1 gain of function significantly increased the susceptibility of mice to experimental colitis, and that was associated with excessive recruitment of dendritic cells and enhanced Th17 immune responses in the lamina propria of colon. TRPV1 gain of function promoted dendritic cell activation and cytokine production upon inflammatory stimuli, and consequently enhanced dendritic cell-mediated Th17 cell differentiation. Further mechanistic studies showed that TRPV1 gain of function in dendritic cells enhanced activation of calcineurin/nuclear factor of activated T cells (NFATc2) signaling induced by inflammatory stimuli. Moreover, in patients with IBD, TRPV1 expression was increased in lamina propria cells of inflamed colon compared with healthy controls. Our findings identify an important role for TRPV1 in modulating dendritic cell activation and sustaining Th17 responses to inflammatory stimuli, which suggest that TRPV1 might be a potential therapeutic target in controlling mucosal immunity and IBD.